Germinação e aspectos morfológicos de sementes de Dypsis leptocheilos (Hodel) Beentje & J. Dransf. (Arecaceae) - Pimenta, Ricardo Soares [UNESP] (2009)
Dypsis leptocheilos (Hodel) Beentje & J. Dransf is a palm highly valued as ornamental. The propagation is by seed. However, there is little information on this process. The objective of this work was to study the morphology, the effect of temperature, substrate and storage on germination of D. leptocheilos seeds. The experiment was conducted at the Faculty of Agriculture and Veterinary Sciences, UNESP/Jaboticabal. The 4 studies conducted were: 1) morphology; 2) temperature effect: the experimental design was randomized with 6 treatments (laboratory condition temperature, 25 ºC, 30 ºC, 35 ºC, 20-30 ºC and 25-35 ºC) and using coconut fiber as substrate; 3) substrate effect, the experimental design was randomized with 4 treatments (coconut fiber, sand, vermiculite and Plantmax ®) and using a temperature of 30 ºC; 4) storage effect: the experimental design was randomized with 5 treatments (4 months of storage and then sowing after harvest) and using vermiculite as substrate in laboratory condition temperature and 4 replications of 25 disseminules to study 2, 3 and 4. For all studies, except for morphology, water replacement in the substrate was made by keeping 100% of the capacity of retention and was made a count of germinated seeds every 2 days being adopted as a criterion of germination the germinative button. To study the effect of temperature and substrate were determined percentage of germination (%G), speed of germination index (SGI), leaf area (cm2), root length and shoot (cm), leaf dry mass (g) and root dry mass (g). The statistical analysis was performed (except for morphology) to study the effect of temperature and substrate, the means were compared using the Tukey test and for storage, polynomial regression was performed. It was concluded that germination of D. leptocheilos is adjacent ligular type, and the condition that provided the greatest percentage and speed of seed... (Complete abstract click electronic access below)